2005
DOI: 10.1590/s0004-282x2005000300009
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulatory effects of caffeine and bromazepam on visual event-related potential (P300): a comparative study

Abstract: The P300 component of the event-related potential (ERP) is a general measurement of "cognitive efficiency". It is an index of the ability of an individual's central nervous system (CNS) to process incoming information. OBJECTIVE: To compare the neuromodulatory effects of caffeine and bromazepam on the visual ERP (P300), in relation to a P300 normative database. METHOD: 15 right-handed individuals (7 male and 8 female), between 20 and 30 years of age, healthy, free of any cognitive impairment and not making use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The authors observed that the longest motor reaction time was noticed 6 hours after the drug ingestion. Montenegro 19 tried to verify whether there would be reaction time changes after ingestion of 3 mg of bromazepam. The authors believed that a longer reaction time would occur, but the expected result was not found.…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed that the longest motor reaction time was noticed 6 hours after the drug ingestion. Montenegro 19 tried to verify whether there would be reaction time changes after ingestion of 3 mg of bromazepam. The authors believed that a longer reaction time would occur, but the expected result was not found.…”
Section: Discussionmentioning
confidence: 99%
“…However, lower amplitude was observed for the caffeine condition, when compared to the normative database and bromazepam. Therefore, the authors stated that caffeine seemed to increase the P300 only when the individuals were tired [35]. Such results suggest that both the caffeine and the modafinil effects, with the utilized dose (200mg), do not improve the cognitive processes, evaluated by the P300 measures.…”
Section: Amplitudementioning
confidence: 98%
“…The preliminary phytochemical analysis of Limonia acidissima plant parts showed the presence of alkaloids, flavonoids, phenols, terpenoids, tannins,fats steroids, saponins, glycosides, gum, mucilage and fixed oils [15][16][17][18]…”
Section: Phytochemicalsmentioning
confidence: 99%